A four-coordinate cadmium(II) polymer for efficient adsorption of Congo red, kinetic, isotherm, fluorescence and antibacterial activity. Issue 19 (2nd October 2017) - Beheshti, Azizolla; Nozarian, Kimia; Abrahams, Carmel T.; Motamedi, Hossein
Abstract: A 3-D cadmium-based coordination polymer, [CdCl2 L]n (1 ) (where L = 1, 1-(1, 6-hexanediyl)bis(1, 3-dihydro-3-methyl-1H-imidazole-2-thione), was synthesized and structurally characterized. The capability of the polymer as an efficient sorbent for Congo red (CR) removal from aqueous solution has been evaluated. Compound1 has a tetrahedral arrangement with a CdS2 Cl2 core. L in1 is bidentate to two neighboring Cd II centers via the methimidazole sulfurs to create 1D chains propagating along the c-axis. The remaining coordination sites are occupied by two terminal chlorides. The chains are further stabilized by intermolecular C–H⋯Cl hydrogen bonds between the chlorides and hydrogens of the imidazole rings. Parallel chains stack in the 3-D structure. The Cd II polymer sorbent was characterized by infrared spectroscopy, elemental analysis, UV–vis, solid fluorescence and X-ray single-crystal diffraction. Sorption kinetics were studied by three kinetic models, second order, Elovich and intraparticle diffusion. The results indicate that the mechanism of the sorption process followed Elovich kinetic model. Sorption equilibrium was also studied with Langmuir, Temkin, and Freundlich isotherm models. The sorption process followed the Temkin isotherm. MIC, MBC, and DNA cleavage activities of1 were also studied. Furthermore, the UV–vis and solid state fluorescence spectra of1 were measured. Abstract :